2016
DOI: 10.1159/000452584
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Monascus Adlay</i></b> and Monacolin K Attenuates Arterial Thrombosis in Rats through the Inhibition of ICAM-1 and Oxidative Stress

Abstract: Background/Aims: Monascus Adlay (MA) prepared from fungal fermentation of Monascus purpureus inoculating with cooked adlay contains high content of monakolin K (MK) and phenolic compounds. We explored whether MA and MK improve FeCl3-induced arterial thrombosis in rats. Methods: The rats were divided into control, FeCl3-treated rat carotid artery occlusion (TTO), TTO determined with one-week MA, and TTO determined with one-week MK. We compared MA or MK effects on oxidative stress by chemil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…The rat ferric chloride model has been used in a number of studies to evaluate thrombosis, particularly in the context of antithrombotic therapies. The controls (no therapy) in our study had an average TTO of~12 min; other studies using various parameters of ferric chloride concentration and time of application, as well as filter paper dimensions, have control TTO data from 7.8-8.7 min [19,20] to greater than 30 min [8,21,22], with many values between these times [23][24][25][26][27][28][29][30][31][32][33]. We selected our particular ferric chloride induction parameters to provide a moderate injury so that heparin therapy might have an influence, as was determined to be the case.…”
Section: Discussionmentioning
confidence: 62%
“…The rat ferric chloride model has been used in a number of studies to evaluate thrombosis, particularly in the context of antithrombotic therapies. The controls (no therapy) in our study had an average TTO of~12 min; other studies using various parameters of ferric chloride concentration and time of application, as well as filter paper dimensions, have control TTO data from 7.8-8.7 min [19,20] to greater than 30 min [8,21,22], with many values between these times [23][24][25][26][27][28][29][30][31][32][33]. We selected our particular ferric chloride induction parameters to provide a moderate injury so that heparin therapy might have an influence, as was determined to be the case.…”
Section: Discussionmentioning
confidence: 62%
“…ICAM‐1, a primary endothelial cell adhesion molecule, interacts with platelet α IIb β 3 through endothelial GPIb‐IX‐V and mediates platelet adhesion. [ 31 ] Studies have indicated that monascus adlay and monacolin K attenuate arterial thrombosis in rats through inhibition of ICAM‐1 in endothelial cells; [ 44 ] ICAM‐1‐targeted thrombomodulin mitigates tissue factor‐driven inflammatory thrombosis, [ 45 ] and endotoxemia‐augmented murine venous thrombosis formation is dependent on ICAM‐1 and TLR‐4. [ 46 ] Consistently, we found that ICAM‐1 expression was upregulated in TAECs after heat treatment, and increased ICAM‐1 expression induced platelet adhesion, aggregation, and activation; ICAM‐1 inhibition or blockade reversed the effects.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the lowering lipid effects, the physiological functions of MLs like promoting bone formation, attenuating arterial thrombosis, and anticancer have also been confirmed (Wong and Rabie, 2008;Tseng et al, 2011;Tien et al, 2016;Xu et al, 2017;Wang et al, 2019). New bone formation in bone defects in vivo and bone cell formation in vitro can be stimulated and increased using RMR extract (Wong and Rabie, 2008).…”
Section: Functions Of Frmrmentioning
confidence: 90%